Long Non-Coding RNA THOR Depletion Inhibits Human Non-Small Cell Lung Cancer Cell Growth - Peng-Fei Jiao (Frontiers Media S.A., 2021)
Long non-coding RNA (LncRNA) THOR (Lnc-THOR) is expressed in testis and multiple human malignancies. Lnc-THOR association with IGF2BP1 (IGF2 mRNA-binding protein 1) is essential for stabilization and transcription of IGF2BP1 targeted mRNAs. We tested its expression and potential functions in non-small cell lung cancer (NSCLC). In primary NSCLC cells and established cell lines, Lnc-THOR shRNA or CRISPR/Cas9-mediated knockout (KO) downregulated IGF2BP1 target mRNAs (IGF2, Gli1, Myc and SOX9), inhibiting cell viability, growth, proliferation, migration and invasion. Significant apoptosis activation was detected in Lnc-THOR-silenced/-KO NSCLC cells. Conversely, ectopic overexpression of Lnc-THOR upregulated IGF2BP1 mRNA targets and enhanced NSCLC cell proliferation, migration and invasion. RNA-immunoprecipitation and RNA pull-down assay results confirmed the direct binding between Lnc-THOR and IGF2BP1 protein in NSCLC cells. Lnc-THOR silencing and overexpression were ineffective in IGF2BP1-KO NSCLC cells. Forced IGF2BP1 overexpression failed to rescue Lnc-THOR-KO NSCLC cells. In vivo, intratumoral injection of Lnc-THOR shRNA adeno-associated virus potently inhibited A549 xenograft tumor growth in nude mice. At last we show that Lnc-THOR is overexpressed in multiple NSCLC tissues and established/primary NSCLC cells. Collectively, these results highlighted the ability of Lnc-THOR in promoting NSCLC cell growth by associating with IGF2BP1, suggesting that Lnc-THOR represents a promising therapeutic target of NSCLC.